Tetracaine – selective electrodes with polymer membranes and their application in pharmaceutical formulation control - Hassan, Ahmed Khudhair; Ameen, Suham Towfiq; Saad, Bahruddin (Elsevier, 2017)
The construction and electrochemical response characteristics of poly(vinyl chloride) (PVC) membrane electrodes for tetracaine hydrochloride (TCH) are described. The sensing membranes incorporating ion-association complexes of tetracaine cation with phosphotungstic acid (PTA) or phosphomolybdic acid (PMA) or Sodium tetraphenyl borate (NaTPB) as electroactive materials and di-n-butyl phthalate (DBPH) or tri-n-butyl phosphate (TBP) as a plasticizer in PVC matrixes were evaluated. The results obtained show the electrodes based on PTA or PMA as electroactive compounds and DBPH as plasticizer with a fast, stable and near-Nernstian response over a wide concentration range (1 · 105–5 · 102 M), with cationic slopes of 55.02 and 52.05 mV decade1 over a pH range of (2.5–6.5). The electrodes show good discrimination of tetracaine from several inorganic cations and sugars. The electrodes were successfully applied for the determination of tetracaine in pharmaceutical formulations.